Simple equations to predict concentric lower-body muscle power in older adults using the 30-second chair-rise test: a pilot study - Wesley N Smith; Gianluca Del Rossi; Jessica B Adams; et al (Clinical Interventions in Aging, 2010)
Wesley N Smith1, Gianluca Del Rossi1, Jessica B Adams1, KZ Abderlarahman2, Shihab A Asfour2, Bernard A Roos1,3,4,5, Joseph F Signorile1,31Department of Exercise and Sport Sciences,2Department of Industrial Engineering, University of Miami, Coral Gables, FL, USA; 3Geriatric Research, Education, and Clinical Center, Bruce W Carter Department of Veterans Affairs Medical Center, Miami, FL, USA; 4Departments of Medicine and Neurology, University of Miami Miller School of Medicine, Miami, FL, USA; 5Stein Gerontological Institute, Miami Jewish Health Systems, Miami, FL, USAAbstract: Although muscle power is an important factor affecting independence in older adults, there is no inexpensive or convenient test to quantify power in this population. Therefore, this pilot study examined whether regression equations for evaluating muscle power in older adults could be derived from a simple chair-rise test. We collected data from a 30-second chair-rise test performed by fourteen older adults (76 ± 7.19 years). Average (AP) and peak (PP) power values were computed using data from force-platform and high-speed motion analyses. Using each participant’s body mass and the number of chair rises performed during the first 20 seconds of the 30-second trial, we developed multivariate linear regression equations to predict AP and PP. The values computed using these equations showed a significant linear correlation with the values derived from our force-platform and high-speed motion analyses (AP: R = 0.89; PP: R = 0.90; P < 0.01). Our results indicate that lower-body muscle power in fit older adults can be accurately evaluated using the data from the initial 20 seconds of a simple 30-second chair-rise test, which requires no special equipment, preparation, or setting.Keywords: instrumental activity of daily living, clinical test, elderly, chair-stand test, leg power